2020
DOI: 10.1097/iop.0000000000001515
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing Morphology Assessments in Oculoplastic Surgery: Reliability and Validity of Lay People Relative to Professional Image Analysts and Experts

Abstract: Purpose: To determine if crowdsourced ratings of oculoplastic surgical outcomes provide reliable information compared to professional graders and oculoplastic experts. Methods: In this prospective psychometric evaluation, a scale for the rating of postoperative eyelid swelling was constructed using randomly selected images and topic experts. This scale was presented adjacent to 205 test images, including 10% duplicates. Graders were instructed to match … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The authors note that the following variables were considered potentially important predictors of MMCR outcomes, but did not achieve statistical significance on bivariate analysis: intraoperative events that increased tissue trauma (slippage of the ptosis clamp requiring repositioning, suture transection requiring re-suturing, and hematoma formation), the degree of edema 26 at the 1-week postoperative visit, the use of a nightly protective eye shield for 1 month after surgery, and the use of prostaglandin drops 27 (eSupplement 3, Supplemental Digital Content, available at http://links.lww.com/IOP/A343).…”
Section: Discussionmentioning
confidence: 99%
“…The authors note that the following variables were considered potentially important predictors of MMCR outcomes, but did not achieve statistical significance on bivariate analysis: intraoperative events that increased tissue trauma (slippage of the ptosis clamp requiring repositioning, suture transection requiring re-suturing, and hematoma formation), the degree of edema 26 at the 1-week postoperative visit, the use of a nightly protective eye shield for 1 month after surgery, and the use of prostaglandin drops 27 (eSupplement 3, Supplemental Digital Content, available at http://links.lww.com/IOP/A343).…”
Section: Discussionmentioning
confidence: 99%
“…Crowdsourcing using unskilled internet users has been used to identify pathological features of diabetic retinopathy [ 19 , 20 , 29 ] and glaucoma [ 18 , 30 ] on fundus photographs as well as to classify surgical outcomes of ophthalmic surgery [ 31 - 33 ]. Aggregating the scores of a “crowd” of skilled graders has also been used in ophthalmology to generate robust consensus annotations of images for artificial intelligence (AI) algorithm training [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crowdsourcing using unskilled internet users has been used to identify pathological features of diabetic retinopathy [19,20,29] and glaucoma [18,30] on fundus photographs as well as to classify surgical outcomes of ophthalmic surgery [31][32][33].…”
Section: Use Of Crowdsourcingmentioning
confidence: 99%
“…A recent study showed that reading center graders were nearly as reliable and accurate as experts for assessment of oculoplastic morphological outcomes, whereas crowdsourced lay observers were less accurate and consistent despite a strong overall correlation between the three groups. 29 Reading centers may be more time- and cost-effective than experts while more reliable than naĂŻve crowdworkers, and could represent a feasible middle ground.…”
Section: Discussionmentioning
confidence: 99%